Analysis of Seaweed Business Income Level at Rawing Mairori in Sarwandori Village, Yapen Regency: Analysis of Seaweed Business Income Level at Rawing Mairori in Sarwandori Village, Yapen Regency - Daniel A. Dawan (Institute of Computer Science (IOCS), 2020)
Analysis of Operating Revenues Seaweed On Mairori in Kampung Sarwandori Rawing Yapen. Objective is to determine the level of income of seaweed products and to determine the factors that influence the level of income of seaweed products in businesses in the village Sarwandori Rawing Mairori Yapen. Results showed that the cost of production has twice earned total net income of Rp 2,352,542, -. Analysis of the income level of seaweed products in businesses in the village Sarwandori Rawing Mairori Yapen financially beneficial to the R / C ratio is2,442, While production levels to reach the breakeven point BEP is Rp 16 016, -. As for the factors that affect the level of seaweed products in businesses in the village Sarwandori Rawing Mairori Yapen namely Labor, Environment Weather / Climate, Capital, Selling Price.